Impact of non-restorative cavity control on proximal carious lesions of anterior primary teeth on the tooth survival and patient-centered outcomes (CEPECO 2): study protocol for a non-inferiority randomized clinical trial - Renata M. D. Bianchi; Aline M. Pascareli-Carlos; Isabela Floriano; Daniela P. Raggio; Mariana M. Braga; Thais Gimenez; Mariana C. Holanda; Gabriela S. da Silva; Karina H. de Natal; Tamara K. Tedesco (BMC, 2021)
Abstract Background Studies have questioned the necessity of restoring cavitated carious lesion on primary teeth, once the control of biofilm is the most important factor to arrest these lesions. This randomized clinical trial aimed to compare the survival of teeth treated with a non-restorative cavity control (NRCC) compared to resin composite restorations (RCR) on proximal carious lesion in anterior primary teeth, as well as the impact of these treatments on patient-centered outcomes. Methods A randomized clinical trial with two parallels arms (1:1) will be conducted. Children between 3 and 6 years old will be selected from the Center of Clinic Research of Pediatric Dentistry of Ibirapuera University (UNIB), a dental trailer (FOUSP) located on Educational Complex Professor Carlos Osmarinho de Lima, the Pediatric Dentistry Clinic of Santa Cecília University and from the Pediatric Dentistry Clinic of University Center UNINOVAFAPI. One hundred and forty-eight teeth will be randomly distributed in two experimental groups: (1) Selective removal of carious tissue and RCR; or (2) NRCC through cavity enlargement using a metallic sandpaper. The primary outcome will be tooth survival after 6, 12, 18 and 24 months. The duration and the cost of dental treatments will be considered for the estimation of the cost-effectiveness of the evaluated treatments. The discomfort reported by the participants will be measured after each treatment using the FIS scale. The participants' satisfaction and perception of the parents/legal guardians will be evaluated through questionnaires. For the primary outcome, Kaplan-Meier's survival and Long-Rank test will be used for comparison between the two groups. All the variables will be modeled by Cox regression with shared fragility. Significance will be considered at 5%. Discussion The NRCC could be an option to manage carious lesions on proximal surfaces of primary teeth, and the approach could be well accepted by the children and parents/legal guardians. Trial registration Clinicaltrials.gov registration: NCT03785730, Registered on December 18th 2018, first participant recruited 30/04/2019, https://clinicaltrials.gov/ct2/show/NCT03785730 . Ethics Reference No: 91569118.8.0000.5597. Trial Sponsor: Universidade Ibirapuera. The Trial was prospectively registered.